Improvement of Critical Current Density in Bi-2223 Superconductor by Ag-Doping - Man, Nguyen Khac; Duc Hoa, Nguyen; Thanh Nhan, Duong Thi (VNU Journal of Science: Mathematics - Physics, 2019)
In this study, high-T c superconducting polycrystalline Bi-2223 undoped sample (A0) and 5wt.% Ag-doped sample (A5) were prepared by solid-state reaction method at 855 0 C with sintering time of 8 days. The X-ray powder diffraction (XRD) results show that the major phase of these samples was Bi-2223. The volume ratio of Bi-2223 phase increased from 78% for undoped sample (A0) to 95% for 5wt.% Ag-doped sample (A5). The enhancement of the onset of high-T c superconductivity (T c,onset = 112.5 K) in silver doping sample was observed by DC-resistivity measurements. From the AC-susceptibility measurements combined with Bean critical state model, the temperature dependent parabolic law of inter-granular or matrix critical current density (J c m ) was fitted. Some J c m values were estimated from these parabolic laws. The results show that 5wt% Ag-doping can nearly double critical current density in the Bi-2223 sample.